Atmospheric parameters of 82 red giants in the Kepler field - Thygesen, Anders (Astronomy and astrophysics, 2012)
Context: Accurate fundamental parameters of stars are essential for the asteroseismic analysis of data from the NASA Kepler mission. Aims: We aim at determining accurate atmospheric parameters and the abundance pattern for a sample of 82 red giants that are targets for the Kepler mission. Methods: We have used high-resolution, high signal-to-noise spectra from three different spectrographs. We used the iterative spectral synthesis method VWA to derive the fundamental parameters from carefully selected high-quality iron lines. After determination of the fundamental parameters, abundances of 13 elements were measured using equivalent widths of the spectral lines. Results: We identify discrepancies in log g and [Fe/H], compared to the parameters based on photometric indices in the Kepler Input Catalogue (larger than 2.0 dex for log g and [Fe/H] for individual stars). The T eff found from spectroscopy and photometry shows good agreement within the uncertainties. We find good agreement between the spectroscopic log g and the log g derived from asteroseismology. Also, we see indications of a potential metallicity effect on the stellar oscillations. Conclusions: We have determined the fundamental parameters and element abundances of 82 red giants. The large discrepancies between the spectroscopic log g and [Fe/H] and values in the Kepler Input Catalogue emphasize the need for further detailed spectroscopic follow-up of the Kepler targets in order to produce reliable results from the asteroseismic analysis.